2020
DOI: 10.1088/1748-9326/ab639a
|View full text |Cite
|
Sign up to set email alerts
|

Fostering collective action to reduce wildfire risk across property boundaries in the American West

Abstract: Large-scale, high-severity wildfires are a major challenge to the future social-ecological sustainability of fire-adapted forest ecosystems in the American West. Managing forests to mitigate this risk is a collective action problem requiring landowners and stakeholders within multi-ownership landscapes to plan and implement coordinated restoration treatments. Our research question is: how can we promote collective action to reduce wildfire risk and restore fire-resilient forests in the American West? To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…Our results contribute to a shared understanding of how diverse land management strategies play out on the landscape. This can contribute to better communication among landowners and with the public, and build the trust necessary to work across ownerships 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results contribute to a shared understanding of how diverse land management strategies play out on the landscape. This can contribute to better communication among landowners and with the public, and build the trust necessary to work across ownerships 16 .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that where highly valued resources are concentrated, strong fire suppression policies will result in disproportionally less area burned regardless of ownership and vegetation type (forest or grass/shrub) and that protected areas will burn more than expected given policies that promote resource objective fire. Results from this analysis broadly inform how fire interacts with different ownerships, a necessary step towards informed discourse to support the collective action that is needed to increase forest resilience and the protection of people and valued resources across all lands 16 .…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, landowners may ignore warnings to manage fuels or may engage in minimal fuel reduction efforts due to differences in forest management interests, the costs associated with these practices, and/or misinformation about the importance of such actions in reducing fire damages. Previous research has raised the question of whether policymakers should introduce financial incentives or fuel regulations to induce individual landowners to undertake increased fuel management activities [12][13][14][15][16]. Prior studies have suggested that cost-share programs and fuel stock regulation could reduce social costs and encourage increased fuel management [2].…”
Section: Introductionmentioning
confidence: 99%